Exclusive radiative Higgs decays as probes of light-quark Yukawa couplings - König, Matthias; Neubert, Matthias (Journal of high energy physics, 2015)
We present a detailed analysis of the rare exclusive Higgs boson decays into a single vector meson and a photon and investigate the possibility of using these processes to probe the light-quark Yukawa couplings.